2022
DOI: 10.7759/cureus.31783
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vitamin B12 Supplementation on Clinical Outcomes in Patients With Diabetic Neuropathy: A Meta-Analysis of Randomized Controlled Trials

Abstract: Diabetic neuropathy (DN) is one of the most prevalent and expensive microvascular consequences of diabetes mellitus (DM), which is noteworthy given that it is frequently both underdiagnosed and undertreated in daily clinical practice. The aim of the current article was to review the efficiency of vitamin B12 supplementation in isolation or in combination therapy for the treatment of diabetic peripheral neuropathy. This meta-analysis was designed according to the Preferred Reporting Items for Systematic Reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(51 reference statements)
0
5
0
1
Order By: Relevance
“…B12 was reported lower in patients with neurofibromatosis type 1 (NF1), hereditary optic neuropathies (HON) and Leber-HON [16], and excessive alcohol consumption populations [17]. B12 supplementation could greatly improve diabetic neuropathic symptoms [18][19][20]. B12 might be the most common risk factor for chronic axonal polyneuropathy (CAPN) in the general population.…”
Section: Vitamin B12mentioning
confidence: 99%
“…B12 was reported lower in patients with neurofibromatosis type 1 (NF1), hereditary optic neuropathies (HON) and Leber-HON [16], and excessive alcohol consumption populations [17]. B12 supplementation could greatly improve diabetic neuropathic symptoms [18][19][20]. B12 might be the most common risk factor for chronic axonal polyneuropathy (CAPN) in the general population.…”
Section: Vitamin B12mentioning
confidence: 99%
“…Algunos autores sugieren el uso profiláctico-preventivo de estas vitaminas en pacientes diabéticos, adultos mayores, pacientes con enfermedades gastrointestinales, vegetarianos y veganos (132)(133)(134)(135)(136). En pacientes con DM que consumen metformina, es particular que por su doble condición de diabéticos y usuarios de metformina, están en mayor riesgo de desarrollar neuropatía periférica, por lo que se recomienda monitoreo de niveles de vitamina B12 (102,104,137).…”
Section: Uso Combinado De Vitaminas B Neurotrópicas Para El Manejo De...unclassified
“…It was found that the B12 supplementation increases the serum B12 level and improves neuropathy symptoms. It was also found that Vitamin B12 can improve neuropathic symptoms and reduce pain in patients with diabetic neuropathy [7]- [10].…”
Section: Introductionmentioning
confidence: 97%